Medical negligence: protection for patients in medical claims / Valzahmer Errino Mohd Tahir, Siti Nur Hafizah Mohd Sokran and Syarina Abdullah Thani - Mohd Tahir, Valzahmer Errino; Mohd Sokran, Siti Nur Hafizah; Abdullah Thani, Syarina (2007)
Medical negligence is defined as a claim against doctors or medical practitioners by the patients in regards to their misconduct. A claim in medical negligence is a traumatic experience for both doctors and patients. Since the Bolam principle was introduced in 1957, the tort of negligence applies an objective standard as a measure of professional conduct, and though it is known as 'fault liability', there is no necessary correlation between a finding that a doctor was negligent in law and a judgment that his conduct was morally blameworthy. The burden of proof lies on the plaintiff. To succeed in his action, the plaintiff must show, first, that there was a breach of duty and second, that the damage flowed from that breach. But it has often been said that the legal concept of causation is not based on logic or philosophy. It is based on the practical way in which the ordinary man's mind works in the everyday affairs of life. Since the Bolam principle is no longer applicable in Malaysia, this study suggests a better protection for patients in medical claims. This is due to the fact that the previous laws being applied by the Malaysian Courts seemed not to be protecting the patients and their rights were jeopardized.